2004
DOI: 10.1159/000077229
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodiagnostic Value of the HER Family in Head and Neck Squamous Cell Carcinoma

Abstract: Two protooncogene products, EGFR (Her-1, c-erbB-1) and HER2 (Her-2/neu, c-erbB-2), have been reported to be frequently overexpressed in head and neck squamous cell carcinoma (HNSCC). In order to identify patients who may benefit from targeted cancer treatment for these two molecules, we determined the expression status of EGFR and HER2 in 129 HNSCC tumor specimens. Two pharmacodiagnostic kits (EGFR pharmDx™ and HercepTest™) were used to identify HNSCC tumors that overexpress EGFR or HER2. Overexpression of EGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
0
17
3
Order By: Relevance
“…Thus, it was suggested as a marker for oral cancer (Li et al, 1992;Xia et al, 1997;Werkmeister et al, 1999;Fong et al, 2008) and also as a prognostic marker (Pinto et al, 2010;Stoicanescu et al, 2013) for monitoring disease progression. However, there is also evidence stating that low/absence of HER2/neu expression in oral cancer (Khan et al, 2002;Schartinger et al, 2004;Henning Hanken et al, 2014). Henning et al demonstrated that Her2 protein and gene amplification was only detectable in a small subset of squamous cell carcinomas of the head and neck region as well as oral squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was suggested as a marker for oral cancer (Li et al, 1992;Xia et al, 1997;Werkmeister et al, 1999;Fong et al, 2008) and also as a prognostic marker (Pinto et al, 2010;Stoicanescu et al, 2013) for monitoring disease progression. However, there is also evidence stating that low/absence of HER2/neu expression in oral cancer (Khan et al, 2002;Schartinger et al, 2004;Henning Hanken et al, 2014). Henning et al demonstrated that Her2 protein and gene amplification was only detectable in a small subset of squamous cell carcinomas of the head and neck region as well as oral squamous cell carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Anomalies in certain oncogenes such as ErbB1 (Her-1), ErbB2, and N-, K-and H-ras have not been found to play a key role in oral cancer (40)(41)(42)(43). When altered, genes that code for the synthesis of cyclin proteins, may act as oncogenes.…”
Section: 88 --------------------------------------------------------mentioning
confidence: 99%
“…One of the favourized targets is the epidermal growth factor receptor (EGFR), a type 1 tyrosine kinase membrane receptor that regulates important cellular functions in epithelial malignancies. EGFR has been found to be frequently overexpressed in head and neck squamous cell carcinomas [29,30]. Overexpression of EGFR has been correlated with worse patient survival in head and neck cancer, although results were not concordant between studies [29][30][31].…”
Section: Blocking Egfr: a New Perspectivementioning
confidence: 99%